Air-assisted bubble immobilization at hydrophilic porous surface. Issue 4 (December 2014) - Zawala, Jan; Kosior, Dominik; Malysa, Kazimierz
Abstract : The article presents experimental results and numerical simulations on influence of air presence at hydrophilic porous surface (fritted glass filter) on kinetics of the bubble collisions and bouncing. Phenomena occurring during collisions of the rising bubble with surface of the fritted glass filter without and with microbubbles sticking out (protruding) of the pores was monitored using a high-speed camera (1000 Hz). It was found that air presence at hydrophilic porous surface affected significantly the collision course, the bouncing amplitude and time of the bubble immobilization (capture). Air presence (microbubbles sticking out) caused that the amplitudes of the bubble position oscillations and the bubble local velocity variations during the collisions were shifted toward smaller time values. Numerical calculations carried out for a model system were in a pretty good agreement with the experimental data obtained. Both sets of data indicate that faster immobilization of the colliding bubble at hydrophilic porous surface was related to a quicker drainage and rupture of foam (water) film formed locally between the colliding macrobubble and submicroscopic bubbles protruding from the hydrophilic surface pores.